REPRESENTASI KONSEP UCHI-SOTO DALAM BAHASA JEPANG - Reny Wiyatasari (KIRYOKU, 2017)
Like a coin, language and culture are two things that can not be separated. Through language, we can see the concept that is owned by a nation. In this article, the author intends to write one of the concepts embraced by Japanese society, namely uchi-soto. The embodiment of this concept is visible from the language they use. The structure in the demontrative pronoun (kosoado), the give-receive verb (jujudoushi), the honorific word (keigo), the forms of personal pronoun are the many Japanese patterns that presenting the uchi- soto. This article aims to explain the form and expression of the basic Japanese use of the concept on the value of uchi-soto through various examples of sentences anad speech. The data used in this article is taken from various libraries, such as from textbooks, short stories and dialogue in Japanese movies.